Biological treatment of olive mill wastewater by non-conventional yeasts - Gonçalves, Cristiana (2009)
The ability of lipolytic yeasts to grow on olive mill wastewater (OMW)-based medium and to produce high-value compounds while degrading this waste, was tested. OMW collected from three-phase olive mills from the North region of Portugal were characterized and used. OMW with COD ranging from 100 g L−1 to 200 g L−1 were supplemented with yeast extract and ammonium chloride. Studies of OMW consumption were carried out in batch cultures of Candida rugosa, Candida cylindracea and Yarrowia lipolytica. All strains were able to grow in the OMW-based media, without dilution, to consume reducing sugars and to reduce COD. C. cylindracea was the best strain concerning the lipase production and the reduction of phenolic compounds and COD. For all strains, the phenols degradation was quite difficult, mostly when more easily degradable carbon source is still present in the medium. Among the phenolic compounds tested catechol is the most inhibitory to the cells.